Outdoor Learning as a Strategy to Improve Young Children’s Language Development - Erna Widiastutik; Arif Budi Wurianto; Mohammad Syaifuddin (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
This study aims to examines the implementation of Outdoor Learning (ODL) as a strategy to enhance early childhood language development at KB Aisyiyah Cakru, Jember. Grounded in the view that early language abilities are fundamental to cognitive, social, and academic growth, ODL was introduced through contextual activities such as visiting a traditional market and exploring a local herbal garden. Using a qualitative descriptive approach, data were collected through observations, semi-structured interviews with teachers and parents, and documentation of children’s learning activities. The findings show that ODL provides authentic, meaningful, and multisensory learning experiences that significantly improve children’s receptive and expressive language skills, including vocabulary acquisition, sentence formation, confidence in communication, and spontaneous verbal interaction. These results align with Vygotsky’s Zone of Proximal Development and the principles of Contextual Teaching and Learning, demonstrating that real-world engagement strengthens language use through social interaction and experiential stimuli. The study concludes that ODL is an effective and relevant pedagogical approach for supporting early language development, particularly in rural PAUD settings rich in local environmental resources.